Antimicrobial properties and release of cinnamaldehyde in bilayer films based on polylactic acid (PLA) and starch. (November 2017) - Muller, Justine; Casado Quesada, Alba; González-Martínez, Chelo; Chiralt, Amparo
Graphical abstract: Highlights: Starch-PLA bilayers films with cinnamaldehyde were obtained by compression moulding. Films exhibited antibacterial effect in in vitro tests against E. coli and L. innocua. Cinnamaldehyde release kinetics depended on both simulant and film. Cinnamaldehyde was tightly bonded to the PLA matrix in PLA bilayer films. Abstract: Cinnamaldehyde (CIN) loaded amorphous PLA films were obtained by casting, using ethyl acetate as solvent. Likewise, bilayer films were obtained by thermocompression of the PLA active layer and compression moulded cassava starch (S) films or semi crystalline PLA films. Starch-PLA laminated materials were considered to improve the barrier capacity (high oxygen barrier through the starch layer and high water vapour capacity through the polyester layer), while CIN incorporation confers antimicrobial activity on the films. The PLA bilayers were obtained for comparison purposes. The antimicrobial activity of the CIN loaded PLA films and S bilayer films was proved against Escherichia coli and Listeria Innocua through in vitro tests, which indicates that the active amount released into the growth medium exceeded the minimum inhibitory concentration (MIC) of both bacteria. The release kinetics of the active compound in different food simulants demonstrated that a part of CIN was tightly bonded to the PLA matrix, whereas the free compound diffused more easily through the starch layer, making S bilayers more active against the bacteria when the starch layer was in direct contact with the culture medium. CIN entrapped in PLA bilayers did not exhibited any antibacterial effect due to its release inhibition, associated to its bonding within the PLA matrix and the lower degree of relaxation in the semi crystalline PLA layer in contact with the food simulants.